Description of Four Dual-Purpose River Buffalo (Bubalis bubalis) Production Systems in Tropical Wetlands of Mexico. Part 2: Sanitary Management, Milking, Zootechnical and Economic Indicators - Bertoni, Aldo; Álvarez-Macías, Adolfo; Morales, Diego Armando; Dávalos, José Luis; Mota-Rojas, Daniel (Journal of Buffalo Science, 2022)
The aim is to elucidate other key aspects of these dual-purpose systems in wetland areas, including labor, markets, the conditions of facilities, machinery and equipment indices, and zootechnical indicators. The health management values determined for production units (PU) PU2, 3, and 4 were similar (50%) but higher at PU1 (75%). Three scheduled milkings once a day (1x), but PU3 performed it twice a day (2x). Most workers are permanent, but PU1 and PU2 hire temporary laborers. The average workday was 7.69 ± 2.84 hours/animal unit at a mean wage of 11.43 ± 1.27. Unit prices per kg of meat from fattening animals and liter of milk were 1.83 ± 0.03 and 0.51 ± 0.08, respectively. Production variables showed an average calving interval of 371.25 ± 7.50 days, a mean parturition index of 89% ± 1%, and mean mortality of 1.8% ± 0.5% and 0.6% ± 0.8% for young and adult animals, respectively. Milk production per lactation was 1240 ± 211.66 liters. The mean daily production for sale was 5.17 ± 0.88 liters. Individual calves consumed 2.13 ± 0.63 liters of milk per day on average. Mean productive life was 17 ± 2.45 years. Average scores on the facilities conditions and machinery and equipment indices were 68% ± 14% and 57% ± 26%, respectively.